Commonalities in the order book - Héléna Beltran-Lopez; Pierre Giot; Joachim G. Grammig (University of Cologne, Centre for Financial Research (CFR), 2009)
This paper uses data from one of the most important European stock markets and shows that, in line with predictions from theoretical market microstructure, a small number of latent factors captures most of the variation in stock specific order books. We show that these order book commonalities are much stronger than liquidity commonality across stocks. The result that bid and ask side as well as the visible and hidden parts of the order book exhibit quite specific dynamics is interpreted as evidence that open order book markets attract a heterogeneous trader population in terms of asset valuations and impatience. Quantifying the informational content of the extracted factors with respect to the evolution of the asset price we find that the factor information shares are highest (about ten percent) for less frequently traded stocks. We also show that the informational content of hidden orders is limited.
Keywords: G10; C32; 330; limit order book; commonalities; liquidity; market microstructure; Wertpapierhandel; Mikrostrukturanalyse; Börsen-Informationssystem; Aktienindex; Deutschland